Impact of Total Quality Management on Operational Performance in Nepalese Commercial Bank - Sah, Aarti; Pradhan, Radhe Shyam (Nepalese Journal of Business, 2025)
This study examines the impact of total quality management on operational performance in Nepalese commercial bank. Operational performance is the dependent variable. The selected independent variables are TQM practices, organizational culture, technology and process improvement, customer relationship management and regulatory compliance. The primary source of data is used to assess the opinions of respondents regarding TQM practices, organizational culture, technology and process improvement, customer relationship management, regulatory compliance and operational performance. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of total quality management on operational performance of Nepalese commercial bank. The study shows that TQM practices is positively correlated to operational performance indicating that better TQM practices lead to increase in operational performance of commercial bank. Similarly, organizational culture is positively correlated to operational performance. It indicates that supportive organizational culture leads to increase in operational performance. Likewise, technology and process improvement are positively correlated to operational performance. It indicates that use of updated technology and process improvement lead to increase in operational performance. Further, customer relationship management is also positively correlated to operational performance. It indicates that practice of customer relationship management lead to increase in operational performance. In addition, regulatory compliance is positively correlated to operational performance. It indicates that effective regulatory compliance leads to increase in operational performance.